Analysis of Letter Filing Procedures at the General Bureau of the Regional Secretariat of North Sumatra Province - Diah Ananda Kharisma; Nur Ahmadi Bi Rahmani (Penerbit Jurnal Indonesia, 2022)
The purpose of this study was to determine the procedures for managing filing documents in the General Administration of the North Sumatra Regional Governor's Office. The examination will also look for obstacles in monitoring the archives of letters and documents in the General Bureau of Business section of the North Sumatra Province Governor's Office. The preparation technique used in this research is a clear qualitative research, with meeting guidelines as the main tool in the interview. The main sources of information used were the head of the General Bureau of the Governor's Office of North Sumatra Province, the Head of Administration of the General Bureau, and employees in the field of archives of the Administrative Section of the General Bureau of the Governor's Office of North Sumatra Province. The inventors used data observation methods based on perceptions, encounters, and documentation. This evaluation found that the implementation of the letter archive in the General Bureau of the North Sumatra Regional Secretariat had been carried out well, but not yet perfect, and usually the administration included recording, storage, maintenance, and transfer. Each report is recorded using a system that includes an agenda book, and expedition book, and decentralized regulations, with each work unit or sub overseeing the capacity of documents or files. Document storage systems use the appropriate form of capacity, and this method uses an alphabetical and numeric framework. This research focuses on the components of the administrative authority of the general bureau of the North Sumatra Province Regional Secretariat in full.